READING ANNE OF GREEN GABLES TROUGH THE LENS OF POST-TRUTH CULTURE - Nissi Adjikusuma, Evelyna (Universitas Negeri Semarang, 2020)
Abstract The post-truth culture is a circumstance when facts are less important than someone’s preferences, or in other words, emotions and feelings are more important than the truth. The post-truth culture happens in all fields of life, including in the literature work. In this study, the writer chooses to analyze Anne of Green Gables, a novel written by a Canadian author, Lucy Maud Montgomery. This classic children’s book tells a story about an eleven-year-old orphan girl named Anne Shirley, who was sent to middle-aged siblings, Marilla and Matthew Cuthbert, who had asked for a boy, not a girl, to help them on their farm. This paper aims to examine the real Lucy Maud Montgomery and a fictional Anne Shirley of Green Gables using the post-truth concept. The study found that Lucy Maud Montgomery is a Canadian author who gave a little touch of her real-life story in her novel. The story fills with the imaginations, emotions, and struggles of Anne Shirley that somehow blurred the borderline between the real life of LM Montgomery and Anne Shirley’s life in the fiction. As people nowadays pay more attention to their impression of a literary work that can touch their feelings rather than the truth behind the work, the readers are not fully informed of the facts that Montgomery’s real life is not as smooth as Anne Shirley’s life.